E-money Academic: Lesson from Literature Visualizing Scientometric Positioning (1968-2019). Issue 1 (February 2021) - Purnomo, A; Firdaus, M; Hasanah, U; Sano, A V D; Prasnowo, M A
Abstract: There is no overview of literature in the area of e-money research which shows the big picture using data from all countries This paper aims to review the status and visual map position of research in the e-money literature indexed Scopus that used a scientometric positioning overview. The research was carried out using bibliometric techniques. Data analysis as well as visualization utilizing VOSViewer program and the Scopus function for analyse search results. In this review, the details collected applied to 3, 011 documents issued from 1968 through 2019. The study reveal that Miller, A. and Chinese Academy of Sciences were the most active individual scientists and affiliated institutions in e-money literature. In emoney, computer science and Lecture Notes in Computer Science Including Subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics were the most areas of study and dissemination sources. There were nine worldwide group maps with collaborative researchers. In order to identify the body of knowledge created from fifty-one years of literature, this study constructed a convergence axis grouping comprising of e-money: Mobile telecommunication system, Electronic cash system, Finance, Profitability, Investments, Intelligent system, abbreviated as MEFPII themes.